Ultrahigh Energy and Power Density in Ni–Zn Aqueous Battery via Superoxide-Activated Three-Electron Transfer - Duan, Yixue; Li, Bolong; Yang, Kai; Gong, Zheng; Peng, Xuqiao; He, Liang; Ho, Derek (Nano-Micro Letters, 2024)
Aqueous Ni–Zn microbatteries are safe, reliable and inexpensive but notoriously suffer from inadequate energy and power densities. Herein, we present a novel mechanism of superoxide-activated Ni substrate that realizes the redox reaction featuring three-electron transfers (Ni ↔ Ni3+). The superoxide activates the direct redox reaction between Ni substrate and KNiO2 by lowering the reaction Gibbs free energy, supported by in-situ Raman and density functional theory simulations. The prepared chronopotentiostatic superoxidation-activated Ni (CPS-Ni) electrodes exhibit an ultrahigh capacity of 3.21 mAh cm−2 at the current density of 5 mA cm−2, nearly 8 times that of traditional one-electron processes electrodes. Even under the ultrahigh 200 mA cm−2 current density, the CPS-Ni electrodes show 86.4% capacity retention with a Columbic efficiency of 99.2% after 10,000 cycles. The CPS-Ni||Zn microbattery achieves an exceptional energy density of 6.88 mWh cm−2 and power density of 339.56 mW cm−2. Device demonstration shows that the power source can continuously operate for more than 7 days in powering the sensing and computation intensive practical application of photoplethysmographic waveform monitoring. This work paves the way to the development of multi-electron transfer mechanisms for advanced aqueous Ni–Zn batteries with high capacity and long lifetime. Highlights: 1 Efficient activation of Ni electrode employs chronopotentiostatic superoxidation. 2 Novel superoxide activation mechanism realizes the redox reaction with three-electron transfer (Ni ↔ Ni3+). 3 As-prepared CPS-Ni||Zn batteries exhibit simultaneously ultrahigh energy and power densities.